Hematologic profiling and spectrum of beta-thalassemia trait in reproductive-age groups - Abbas, Hina; Ahmed, Naseem; Fareed , Noorulain; Urooj, Ifrah; Anwer, Ghania; Barkah , Aimen (International Journal of Pathology, 2025)
Background: Beta thalassemia trait (BTT) is a common inherited hemoglobinopathy in Pakistan. These individuals remain asymptomatic and can pass this gene to their offspring, leading to an increased burden of disease, especially in a resource-limited setting. Our objective is to determine the frequency of BTT among individuals aged 15–49 years using CBC and HPLC parameters.Methods: It is a retrospective cross-sectional study conducted in the central lab of Dr. Ruth K. M. Pfau Civil Hospital, Karachi. Patients whose High-Performance Liquid Chromatography (HPLC) and CBC tests were done between June 2022 to June 2024 were included. All patients of the reproductive age group (15-49 according to WHO) are included. Different CBC parameters such as Hb, Mean Cell Volume (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Cell Hemoglobin Concentration (MCHC) and Hct, along with the percentage level of different Hb variants like HbA2, HbF, HbS, HbC, HbD, and HbE.HbA2 were analysed. Statistical Package for Social Sciences version 25 (SPSS) was used for statistical data analysis. Results: Study analyzed 176 patients, consisting of 101 females (57.4%) and 75 males (42.6%). Among these, 49 patients exhibited abnormal HPLC results while 127 had normal results. The frequency of BTT was higher in females than in males. Among the three age groups, 15-24, 25-34, and 35-49 years, the highest incidence of BTT was seen in the 25-34 age range, where 20 cases were identified. It was also noted that individuals with BTT tend to have higher average hemoglobin and hematocrit levels, along with lower MCV levels compared to normal individuals. Conclusion: Frequency of BTT is high in the reproductive age group. Significant differences are observed in hematological indices between BTT and normal individuals, especially in MCV, MCH, and RBC counts. HbA2 levels >3.5% on HPLC proved to be a reliable marker for diagnosing BTT.